A Digital-Based Optimal AVR Design of Synchronous Generator Exciter Using LQR Technique - Ibraheem Kasim Ibraheem (Al-Khwarizmi College of Engineering – University of Baghdad, 2011)
In this paper a new structure for the AVR of the power system exciter is proposed and designed using digital-based LQR. With two weighting matrices R and Q, this method produces an optimal regulator that is used to generate the feedback control law. These matrices are called state and control weighting matrices and are used to balance between the relative importance of the input and the states in the cost function that is being optimized. A sample power system composed of single machine connected to an infinite- bus bar (SMIB) with both a conventional and a proposed Digital AVR (DAVR) is simulated. Evaluation results show that the DAVR damps well the oscillations of the terminal voltage and presents a faster response than that of the conventional AVR.